Ammonia borane, a material with exceptional properties for chemical hydrogen storage. (13th April 2017) - Demirci, Umit B.
Abstract: Ammonia borane H3 NBH3, first reported in 1955, is isoelectronic with ethane H3 CCH3, but it has much different properties owing to ( i ) the nitrogen and boron atoms (leading to a dipole moment), ( ii ) the protic and hydridic hydrogens, and ( iii ) the heteropolar dihydrogen bonding (rationalizing its solid state at ambient conditions). Ammonia borane has exceptional properties for chemical hydrogen storage and the recent years have witnessed many efforts in making it implementable for both thermolytic and hydrolytic dehydrogenations. The present article aims at ( 1 ) giving an exhaustive overview of the 1955–2016 literature dedicated to ammonia borane's fundamentals and exceptional properties, and then ( 2 ) surveying the main achievements, limitations and challenges for chemical hydrogen storage. Graphical abstract: Highlights: Ammonia borane H3 NBH3 has attractive properties owing to the N and B atoms. Ammonia borane has in fact exceptional properties for chemical hydrogen storage. Ammonia borane is implementable for thermolytic and hydrolytic dehydrogenations. An exhaustive overview of the 1955–2016 literature is given herein. The main achievements, limitations and challenges are surveyed.